2014
DOI: 10.1007/s12325-014-0110-3
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Patterns Following Discontinuation of Adalimumab, Etanercept, and Infliximab in a US Managed Care Sample

Abstract: Restarting of index TNF-blocker therapy occurs frequently after discontinuation, suggesting that long gaps in TNF-blocker therapy may be common. A significantly higher proportion of etanercept patients restarted their index TNF blocker within 3 months of discontinuation, compared with adalimumab and infliximab patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…106 Although a majority (61% to 66%) of patients restarted therapy within 3 months after initial discontinuation, the study confirmed that long gaps in the treatment of psoriasis, PsA, and RA are common (differences across the disease entities were insignificant). 106 Interestingly a significantly higher proportion of etanercept patients restarted etanercept within 3 months of discontinuation, compared with patients taking adalimumab or infliximab. 106 Also in 2014, Jani and colleagues 154 published results of a United Kingdom survey of 548 PsA patients, 94 of whom were switched at least once from a TNF-a inhibitor to a second or third PsA therapy.…”
Section: Treatment Resistance and Disease Recurrence/complications Trmentioning
confidence: 62%
See 4 more Smart Citations
“…106 Although a majority (61% to 66%) of patients restarted therapy within 3 months after initial discontinuation, the study confirmed that long gaps in the treatment of psoriasis, PsA, and RA are common (differences across the disease entities were insignificant). 106 Interestingly a significantly higher proportion of etanercept patients restarted etanercept within 3 months of discontinuation, compared with patients taking adalimumab or infliximab. 106 Also in 2014, Jani and colleagues 154 published results of a United Kingdom survey of 548 PsA patients, 94 of whom were switched at least once from a TNF-a inhibitor to a second or third PsA therapy.…”
Section: Treatment Resistance and Disease Recurrence/complications Trmentioning
confidence: 62%
“…Some investigators have suggested combination therapy (see later discussion) or switching from one biologic to another to improve clinical efficacy in PsA, although this has not been supported by clinical evidence. 105,106 A 2012 meta-analysis performed an indirect comparison of PsARC and patientreported outcomes for the available anti-TNF agents at that time (adalimumab, etanercept, golimumab, and infliximab). 107 Data from 20 publications representing 7 PsA clinical trials were analyzed; the investigators and did not find any statistically significant differences between the TNF-a inhibitors, 107 as the data compiled in Table 2 also suggest.…”
Section: Disease-modifying Antirheumatic Drugsmentioning
confidence: 99%
See 3 more Smart Citations